2016
DOI: 10.2495/sdp-v11-n4-578-587
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local and regional air pollution on atmospheric measurements in Ny-Ålesund

Abstract: The Zeppelin observatory is a research station near the village Ny-Ålesund in Svalbard. The facility delivers data to international projects devoted to high data quality monitoring of the background air pollution in the Arctic. An approach for quantifying the influence of local and regional pollution on measurements that may be misinterpreted as long-range transported one, is presented here.The hourly gas and aerosol data measured in Ny-Ålesund and at the Zeppelin station, respectively, have been analysed alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Firstly, long-range transported pollution prevailing in the Arctic in winter and spring decreases in summer because of the change in the position of the Arctic Front, which prevents effective south-to-north longrange air transport (AMAP 2006). Secondly, there are few local anthropogenic sources of air pollution in the Artic and some of them have intermittent emission rates, e.g., ship traffic (Dekhtyareva et al 2016). Thirdly, the conversion rate of SO 2 to SO 4 2increases in summer, a process governed by two major mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, long-range transported pollution prevailing in the Arctic in winter and spring decreases in summer because of the change in the position of the Arctic Front, which prevents effective south-to-north longrange air transport (AMAP 2006). Secondly, there are few local anthropogenic sources of air pollution in the Artic and some of them have intermittent emission rates, e.g., ship traffic (Dekhtyareva et al 2016). Thirdly, the conversion rate of SO 2 to SO 4 2increases in summer, a process governed by two major mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…This institute also provided hourly temperature, pressure, relative humidity, wind speed and wind direction data obtained at the two stations. Previous studies have shown that the local wind measurements at the Zeppelin station are subject to a wind-shielding effect from nearby mountains, so these data cannot be used for comparison with measurement results from Ny-Ålesund (Dekhtyareva et al 2016). Therefore, atmospheric stratification and local wind flows in the lowest atmosphere (0-500 m height) were studied using atmospheric radiosoundings performed by the Alfred Wegener Institute in Ny-Ålesund.…”
Section: Study Area and Materialsmentioning
confidence: 99%
See 3 more Smart Citations